Physico-chemical characterization and application of the water-soluble polysaccharides extracted from Retama raetam seeds - Ghoul Inas; Mazouzi Roumaissa; Necib Asma; Ouaar Hadjer (Université of Eloued, 2024)
This study aimed to extract and to characterize the water-soluble polysaccharides from Retama raetam seeds harvested from the El Oued region and to apply it as edible biopolymer for food packaging. The sugar was extracted by hot water maceration followed by ethanol precipitation, Total sugars, neutral sugars, polyphenols, and proteins contenants were mesured. Structural properties of the extract were studied using UV-Visible, FTIR, XDR , and SEM-EDX technic. Biofilms was prepared at different concentrations, and thickness, opacity, moisture content, water contact angle, and solubility were measured. Then, the biofilm was applied in cheese packaging. Results showed an extraction yield equal to 7%. Chemical analysis of the raw sugar extract revealed a total sugar concentration of was 70%. The neutral sugar content was approximately 54,60%. Protein content was 6,27%. Polyphenol content was 1,7%. Structural characterization confirmed that the polysaccharides is of galactomannans type. Biofilms were prepared at two concentrations (1% and 1,5%) thickness measurements were 0,195 mm and 0,226 mm, respectively. While opacity were 0,303% and 0,024%, respectively. However, moisture content were 20% and 14%, respectively. Both biofilms exhibited 100% solubility in Water. Either the contact angle with water was 0° for the two biofilms. The Tests conducted on cheese demonstrated the effectiveness of the biopolymer biofilms in preserving the integrity in terms of gloss, color, appearance, and odor under different conditions (25°C and 4°C), as indicated by pH measurements, cheese weight, and protein and fat oxidation tests which showed weak oxidation. Regarding the biological activity of the biofilms, the result showed an antioxidant activity by the inhibition of the DPPH radical with an IC50 values of 0,40 Mg/ml and 0,46 Mg/ml for the 1% and 1,5% biofilm respectively. Either, the potential antibactrial activity against two bacterial strains was observed at different concentrations, resulting in inhibition zones ranging from 0,40 mm to 2,06 mm for Salmonella enterica and E.coli. In conclusion, this study developed that the obtained biofilms have potential applications in food packaging, due to their ability to preserve food integrity and inhibit bacterial growth
Keywords: Retama raetam; galactomannan; biofilms; cheeze packaging; antibactrial activity; antioxidant activity